This handy Spectrum Math Grade 4 Answer Key Chapter 1 Lesson 1.1 Adding 1- and 2-Digit Numbers provides detailed answers for the workbook questions.

Adding and Subtracting 1 and 2 Digits

If 6 + 3 = 9, then 60 + 30 = 90.

Question 1.
a.

Explanation:
Adding the ones we get 1 + 8 = 9
Adding the tens we get 1 + 0 = 1
So, the sum of both addends 11 and 8 is 19
11 + 8 = 19

b.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get 1 + 3 = 4
So, the sum of both addends 10 and 30 is 40
10 + 30 = 40

c.

Explanation:
Adding the ones we get 5 + 4 = 9
Adding the tens we get 2 + 1 = 3
So, the sum of both addends 25 and 14 is 39
25 + 14 = 39

d.

Explanation:
Adding the ones we get 1 + 8 = 9
Adding the tens we get 8 + 1 = 9
So, the sum of both addends 81 and 18 is 99
81 + 18 = 99

e.

Explanation:
Adding the ones we get 2 + 7 = 9
Adding the tens we get 5 + 1 = 6
So, the sum of both addends 52 and 17 is 69
52 + 17 = 69

f.

Explanation:
Adding the ones we get 4 + 3 = 7
Adding the tens we get 7 + 2 = 9
So, the sum of both addends 74 and 23 is 97
74 + 23 = 97

Question 2.
a.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get 1 + 8  = 9
So, the sum of both addends 10 and 80 is 90
10 + 80 = 90

b.

Explanation:
Adding the ones we get 7 + 2 = 9
So, the sum of both addends 7 and 2 is 9
7 + 2 = 9

c.

Explanation:
Adding the ones we get 5 + 4 = 9
Adding the tens we get 1 + 0  = 1
So, the sum of both addends 15 and 4 is 19
15 + 4 = 19

d.

Explanation:
Adding the ones we get 7 + 2 = 9
Adding the tens we get  0 + 9 = 9
So, the sum of both addends 7 and 92  is 99
7 + 92 = 99

e.

Explanation:
Adding the ones we get 1 + 6 = 7
Adding the tens we get  7 + 0 = 7
So, the sum of both addends 71 and 6 is 77
71 + 6 = 77

f.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get  7 + 1 = 8
So, the sum of both addends 70 and 10 is 80
70 + 10 = 80

Question 3.
a.

Explanation:
Adding the ones we get 7 + 2 = 9
Adding the tens we get  0 + 2 = 2
So, the sum of both addends 7 and 22 is 29
7 + 22 = 29

b.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get  2 + 3 = 5
So, the sum of both addends 20 and 30 is 50
20 + 30 = 50

c.

Explanation:
Adding the ones we get 2 + 7 = 9
Adding the tens we get  9 + 0 = 9
So, the sum of both addends 92 and 7 is 99
92 + 7 = 99

d.

Explanation:
Adding the ones we get 3 + 6 = 9
Adding the tens we get  8 + 1 = 9
So, the sum of both addends 83 and 16 is 99
83 + 16 = 99

e.

Explanation:
Adding the ones we get 6 + 3 = 9
Adding the tens we get  4 + 2 = 6
So, the sum of both addends 46 and 23 is 69
46 + 23 = 69

f.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get  7 + 2 = 9
So, the sum of both addends 70 and 20 is 90
70 + 20 = 90

Question 4.
a.

Explanation:
Adding the ones we get 2 + 1 = 3
Adding the tens we get  0 + 4 = 4
So, the sum of both addends 2 and 41 is 43
2 + 41 = 43

b.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get  3 + 3 = 6
So, the sum of both addends 30 and 30 is 60
30 + 30 =60

c.

Explanation:
Adding the ones we get 1 + 8 = 9
Adding the tens we get  5 + 4 = 9
So, the sum of both addends 51 and 48 is 99
51 + 48 = 99

d.

Explanation:
Adding the ones we get 4 + 4 = 8
Adding the tens we get  3 + 2 = 5
So, the sum of both addends 34 and 24 is 58
34 + 24 = 58

e.

Explanation:
Adding the ones we get 7 + 2 = 9
Adding the tens we get  0 + 2 = 2
So, the sum of both addends 7 and 22 is 29
7 + 22 = 29

f.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get 2 + 5 = 7
So, the sum of both addends 20 and 50 is 70
20 + 50 = 70

Question 5.
a.

Explanation:
Adding the ones we get 0 + 5 = 5
Adding the tens we get 3 + 1 = 4
So, the sum of both addends 30 and 15 is 45
30 + 15 = 45

b.

Explanation:
Adding the ones we get 1 + 1 = 2
Adding the tens we get 2 + 2 = 4
So, the sum of both addends 21 and 21 is 42
21 + 21 = 42

c.

Explanation:
Adding the ones we get 7 + 2 = 9
Adding the tens we get 0 + 4 = 4
So, the sum of both addends 7 and 42  is 49
7 + 42 = 49

d.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get 4 + 4 = 8
So, the sum of both addends 40  and 40 is 80
40 + 40 = 80

e.

Explanation:
Adding the ones we get 7 + 2 = 9
Adding the tens we get  0 + 2 = 2
So, the sum of both addends 7 and 22 is 29
7 + 22 = 29

f.

Explanation:
Adding the ones we get 0 + 0 = 0
Adding the tens we get 2 + 5 = 7
So, the sum of both addends 20 and 50 is 70
20 + 50 = 70

Question 6.
a.

Explanation:
Adding the ones we get 4 + 4 = 8
Adding the tens we get  3 + 3 = 6
So, the sum of both addends 34  and 34 is 68
34 +34 = 68

b.

Explanation:
Adding the ones we get 0 + 3 = 3
Adding the tens we get  6 + 1 = 7
So, the sum of both addends 60 and 13 is 73
60 + 13 = 73

c.

Explanation:
Adding the ones we get 9 + 0 = 9
Adding the tens we get  0 + 3 = 3
So, the sum of both addends 9 and 30 is 39
9 + 30 = 39

d.

Explanation:
Adding the ones we get  4 + 3 = 7
So, the sum of both addends 4 and 3 is 7
4 + 3 = 7

e.

Explanation:
Adding the ones we get 3 + 6 = 9
Adding the tens we get  1 + 0 = 1
So, the sum of both addends 13 and 6 is 19
13 + 6 = 19

f.

Explanation:
Adding the ones we get 4 + 3 = 7
Adding the tens we get  4 + 3 = 7
So, the sum of both addends 44 and 33 is 77
44 + 33 = 77

Question 7.
a.

Explanation:
Adding the ones we get 3 + 2 = 5
Adding the tens we get  0 + 3 = 3
So, the sum of both addends 3 and 32 is 35
3 + 32 = 35

b.

Explanation:
Adding the ones we get 5 + 0 = 5
Adding the tens we get  0 + 1 = 1
So, the sum of both addends 5 and 10 is 15
5 + 10 = 15

c.

Explanation:
Adding the ones we get 3 + 4 = 7
Adding the tens we get  6 + 2 = 8
So, the sum of both addends 63 and 24 is 87
63 + 24 = 87

d.

Explanation:
Adding the ones we get 1 + 0 = 1
Adding the tens we get  7 + 2 = 9
So, the sum of both addends 71 and 20 is 91
71 + 20 = 91

e.

Explanation:
Adding the ones we get 1 + 8 = 9
Adding the tens we get  4 + 0 = 4
So, the sum of both addends 41 and 8 is 49
41 + 8 = 49

f.